The Dynamics of the Bengkulu Tabot: from Sacred to Profan - Agus Sapriansa; Arditya Prayogi (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2022)
Abstract: This article was written with the background that there is a double meaning to the implementation of the Tabot Tradition. This interpretation causes the implementation of Tabot in Bengkulu to change its function. From the beginning, which was sacred-magical belonging to a certain community, it developed into a profane festival belonging to the Bengkulu people with all the festive attributes displayed. This article is a qualitative researchs using historical research methods. The stages of the research carried out were heuristics, verification, interpretation, and historiography. From the results of the analysis, it is known that the Tabot tradition in Bengkulu was originally sacred. Its implementation is closely related to the entry of Shia-Punjab understanding to Bengkulu. In its implementation, the Tabot tradition is recorded in the Story of Tabot script which has a sacred dimension. However, along with the times, the implementation of the Tabot tradition later turned into a festival with the identity of Development Tabot which was introduced by the Bengkulu Government. This condition then resulted in the emergence of a debate related to the legality of identity in the Tabot tradition in Bengkulu. Keywords:Tradition, Tabot, Bengkulu, Sacred, Profan